2012
DOI: 10.1378/chest.11-2297
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of VTE in Nonorthopedic Surgical Patients

Abstract: (Grade 2C) prophylaxis be used other than early ambulation. For patients at low risk for VTE ( ‫ف‬ 1.5%), we suggest mechanical prophylaxis, preferably with intermittent pneumatic compression (IPC), over no prophylaxis (Grade 2C). For patients at moderate risk for VTE ( ‫ف‬ 3%) who are not at high risk for major bleeding complications, we suggest low-molecular-weight heparin (LMWH) (Grade 2B), low-dose unfractionated heparin (Grade 2B), or mechanical prophylaxis with IPC (Grade 2C) over no prophylaxis. For pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
791
2
30

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,853 publications
(836 citation statements)
references
References 183 publications
(207 reference statements)
13
791
2
30
Order By: Relevance
“…However, an increased risk of bleeding and cardiac tamponade resulting from pharmacological thromboprophylaxis remains a major concern for patients who have undergone cardiac surgery 4. Indeed, the latest American College of Chest Physicians evidence‐based clinical practice guidelines on antithrombotic therapy and prevention of thrombosis have also stressed that patients after cardiac surgery are at high risk of major bleeding complications with only moderate risk for VTE (Grade‐2C), and suggested that pharmacological VTE prophylaxis is only needed for those with prolonged hospitalization postsurgery 5. These Grade‐2C recommendations were mainly based on consensus among experts or weak evidence.…”
mentioning
confidence: 99%
“…However, an increased risk of bleeding and cardiac tamponade resulting from pharmacological thromboprophylaxis remains a major concern for patients who have undergone cardiac surgery 4. Indeed, the latest American College of Chest Physicians evidence‐based clinical practice guidelines on antithrombotic therapy and prevention of thrombosis have also stressed that patients after cardiac surgery are at high risk of major bleeding complications with only moderate risk for VTE (Grade‐2C), and suggested that pharmacological VTE prophylaxis is only needed for those with prolonged hospitalization postsurgery 5. These Grade‐2C recommendations were mainly based on consensus among experts or weak evidence.…”
mentioning
confidence: 99%
“…More than half of VTE events occur in association with hospitalization or major surgery; many are thought to be preventable. [1][2][3][4][5] The Centers for Medicare and Medicaid Services (CMS), Centers for Disease Control and Prevention (CDC), and the Agency for Healthcare Research and Quality (AHRQ), 6-9 among other organizations, have identified VTE as a potentially preventable "never" event. Evidence-based guidelines and resources exist to help support hospital-acquired venous thromboembolism (HA-VTE) prevention.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence-based guidelines and resources exist to help support hospital-acquired venous thromboembolism (HA-VTE) prevention. [1][2][3][4][5][6][7][8][9][10] Harborview Medical Center, a tertiary referral center with more than 17,000 patients hospitalized annually, many requiring surgery, serves one of the highest-risk populations for HA-VTE development. Despite high rates of VTE prophylaxis in accordance with an established institutional guideline, 11,12 VTE remains the most common hospital-acquired condition in our institution.…”
Section: Resultsmentioning
confidence: 99%
“…It is now accepted that screening studies that identify asymptomatic DVT overestimate the incidence of clinical VTE and the benefit of LMWH 8, 9, 33. Although asymptomatic DVT has been reported in 10–40% of medical and surgical patients, symptomatic VTE occurs in fewer than 5% 7, 12, 17, 18. Yet screening studies of women after CD have found asymptomatic DVT in fewer than 1% (3/560) 34, 35, 36, 37, 38.…”
Section: Overestimating the Incidence Of Vtementioning
confidence: 99%
“…The use of scoring systems to estimate the post‐surgical incidence of VTE was qualified and a minimum risk of 3% is now deemed necessary to warrant chemoprophylaxis in abdominal/pelvic surgical patients 10, 11, 12. After orthopaedic surgery, less aggressive prophylaxis is now considered acceptable 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%